Fluoroscopic Estimation of Thoracic Dimensional Changes in Healthy Dogs. (29th September 2017) - Chan, J.C.; Johnson, L.R.; Brown, C.S.; Pollard, R.E.
Abstract : Background: Current methods available for assessing alterations in lung mechanics require sophisticated equipment and are of limited availability. A method that could assess lung area change with respiration might be a clinically useful surrogate for assessing lung compliance. Objective: To use fluoroscopy to determine percent change in thoracic and lung areas in healthy dogs. Animals: Forty‐four client‐owned dogs with no evidence of respiratory disease. Methods: Prospective study. Resting respiration was recorded fluoroscopically, and peak inspiratory and expiratory frames were captured for 3 typical respiratory cycles. The number of intrathoracic pixels in the entire thoracic cavity was measured for both inspiration and expiration, and the average percent change in intrathoracic area was determined for each dog. This process was repeated by a hemithorax measurement of lung area that excluded the mediastinum and cardiac silhouette. Proposed reference ranges (and 95% confidence intervals [CI]) were computed by a nonparametric percentile distribution. Results: Median percent change in thoracic dimension for the total thorax measurement was 12.5% (CI, 8.9–24.0%). Median percent change for the hemithorax measurement was significantly ( P < 0.001) larger (20.8%, CI, 14.3–37.6%). Both measurement techniques were correlated with body weight but not with age, sex, thoracic conformation, body condition score (BCS), or breed. Conclusions and Clinical Importance: Fluoroscopy allows a noninvasive and repeatable measure of lung area changes during respiration that must be corrected for body weight. Additional studies in dogs with respiratory diseases are needed to determine its utility in detecting clinically useful alterations in lung area changes.